A High C-Reactive Protein Level on Postoperative Day 7 Is Associated With Poor Survival of Patients With Pancreatic Ductal Adenocarcinoma After Resection. Issue 8 (August 2022) - Tani, Masaji; Iida, Hiroya; Maehira, Hiromitsu; Mori, Haruki; Miyake, Toru; Kaida, Sachiko
Introduction: Pancreatic ductal adenocarcinoma (PDAC) is a common malignancy. While inflammation-related biomarkers influence patient survival after resection, it has not been known whether postoperative inflammations affect the survival of PDAC patients or not. Methods: It was investigated whether the universal biomarkers on postoperative day (POD) 7 affect the survival of PDAC patients in the retrospective view, and univariate and multivariate analyses were performed via the Cox regression method. Results: Overall, 108 consecutive patients underwent resection; 98 (90.7%) had T3 disease and 73 (67.6%) had lymph node metastases. Thirty-four patients (31.5%) experienced postoperative complications. Compared with preoperative values, the white blood cell count and C-reactive protein (CRP) level on POD 7 were significantly elevated ( P < .001 for both); conversely, the lymphocyte count was significantly reduced ( P < .001). Among 108 patients, 72 received adjuvant chemotherapy. The median overall survival was 21.0 months; the 5-year survival rate was 22.3%. On multivariate analysis, receiving adjuvant chemotherapy and low CRP levels on POD 7 (<7.6 mg/dL) were prognosticators of better survival. However, the CD classification was not a prognosticator of survival after resection. Conclusions: Adjuvant chemotherapy and postoperative low CRP levels on POD 7 were prognosticators of better survival of PDAC patients after resection. Surgeons should be aware of managing postoperative infections because a high postoperative CRP level is related with unfavorable survival.